Taking publication date into consideration: a response to the review of Mobile Technologies for Every Library - Lisa Mastin (Journal of the Medical Library Association, 2018)
Comment on Becker D. Mobile technologies for every library [review]. J Med Libr Assoc. 2017 Jul;105(3):296–7. DOI: http://dx.doi.org/10.5195/jmla.2017.269.